ANALISIS PERILAKU BELAJAR DALAM PEMBELAJARAN INTERAKTIF DI KOMUNITAS EDUKARYA - Bintang Ulina Siregar, Rizki Setiawan (JURNAL PENELITIAN PENDIDIKAN SOSIAL HUMANIORA, 2026)
This study aims to analyze the implementation of interactive learning strategies in fostering positive learning behaviors among students in the Edukarya Teaching Community, Kampung Penggilingan Baru, North Bekasi, as a non-formal educational community. The study employs a qualitative approach with a narrative design, utilizing participatory observation, semi-structured interviews, and documentary analysis, which are inductively analyzed using a symbolic interactionism framework. The results indicate that the interactive approach successfully fosters positive learning behaviors, as evidenced by students’ active participation, willingness to present in front of the class, and in educational games. These behaviors were influenced by internal factors such as motivation, interest in learning, and self-confidence, as well as external factors including two-way communication between teachers and students, peer interaction, and a conducive classroom atmosphere. The use of digital media, educational game activities, and a reward system proved effective in providing students with a space to express themselves without fear. An analysis through the lens of symbolic interactionism reveals that the interaction between teachers and students plays a key role in shaping the meaning of learning. Students perceive the learning process not merely as a transfer of knowledge, but as an experience that liberates and opens up space for exploring one’s potential. This study concludes that interactive learning strategies can create an inclusive and engaging learning environment, while also offering practical implications for the development of learning models in non-formal education communities.